The Influence of Hygiene Behavior, Social Capital, and Family Finance Management on Family Welfare Condition - Gusti Pirandy; Isbandi Rukminto Adi (Universitas Medan Area, 2022)
This study aims to describe and analyze the relationship between hygiene behavior, social capital, and family financial management to the condition of family welfare. The problem is focused on the condition of family welfare in rural communities which is often considered low. Then the government's development policy was blamed for not paying attention to remote areas. However, many factors affect welfare conditions. Some of the most frequently associated come from economic, social, and health aspects. In this article, we will show related factors from these 3 aspects, namely hygiene behavior, social capital, and family financial management. The data were collected through descriptive methods and analyzed with a quantitative approach. The research respondents were 400 family heads living in Babakan Madang District, Bogor Regency. This study concludes that there is a significant relationship between hygiene behavior, social capital, and family financial management on family welfare conditions.